A Benign, Small-Scale Power Unit for the Arctic: The Carnot Cycle Concept - Lock, G.S.H. (ARCTIC, 1989)
Small amounts of useful power may be generated in polar or subpolar regions during the winter period by placing a heat engine between a large body of water (near 0 degrees C), acting as a heat source, and the atmosphere (near -25 degrees C), acting as a heat sink. The scheme consists of a fuelless modular system operating on the Carnot cycle. Power is extracted by a reciprocating vapour engine drawing saturated vapour from a water-heated evaporator and exhausting to an air-cooled condenser from which nearly saturated liquid is returned to the evaporator using a reciprocating feed pump. The thermal performance model incorporates both the engine cycle power and the parasitic losses, the latter being incurred as a result of circulating the working fluid (ammonia), pumping water through the evaporator and blowing air through the condenser. Curves indicate power levels in excess of 1 kW, with thermal efficiencies around 5%. The power curves show a maximum with respect to speed. The principal difficulties with this scheme are in heat exchanger design in near-freezing water. The principal advantages are small power levels, flexibility through modular construction and reduction of the capital and operating costs associated with the supply of energy to northern regions.Key words: alternative energy, Carnot, OTEC, heat engine, power Mots clés: énergie alternative, Carnot, conversion de l’énergie thermique de l’océan, machine thermique, force motrice